Arkitektur og pedagogikk i samspill eller motspill? - om betydning av koherens mellom planlegging og etablering av nye typer barnehagebygg - Randi Evenstad; Aslaug Andreassen Becher (Nordisk Barnehageforskning, 2015)
Abstract: This article discusses the intentions and experiences from architects and pedagogues involved in planning and establishing kindergartens with new building topologies in Oslo. The National Kindergarten effort (St.meld.nr. 24 2002-2003) with the political aim that all children between one and six years should have the right to attend kindergarten, led to a huge development of kindergarten buildings all over Norway. Many of the buildings were designed as new typologies named base and zone kindergartens. There are barely research on processes and consequences of the changes in physical structures in educational institutions. The results of the research presented here are based on a case study of processes in four municipalities in Oslo. It shows that the staff working in the new buildings had scarcely any knowledge of the intentions behind the new design, and the support in  establishing pedagogical work in new physical frames was limited. The aim of the article is to expand the knowledge about connections between architecture and pedagogic, and point to the importance of involving the staff/professionals in educational changes where the physical environment is at stake. These findings may be relevant to other transformations involving organizational and architectural changes.